ANALYSIS OF LITERACY CAPABILITY ACHIEVEMENTS FROM THE MINIMUM COMPETENCY ASSESSMENT RESULTS IN THE EDUCATION REPORT OF HIGH SCHOOL LEVEL IN OGAN ILIR REGENCY - HASNIYATI, SYARI; SUSANTI, RAHMI; RAHARJO, MAKMUM (LEARNING : Jurnal Inovasi Penelitian Pendidikan dan Pembelajaran, 2024)
The aim of the research is to analyze the literacy abilities of students as a result of the Minimum Competency Assessment on high school level education reports. The research method used is descriptive qualitative. The data collected is the achievement of students' literacy skills as a result of the minimum competency assessment on high school level education reports. The research sample was taken randomly as many as 50% from high schools in Ogan Ilir Regency. The research results show that the average literacy ability of high school students in Ogan Ilir district reaches the minimum competency of 54%, the remaining 46% have not reached the minimum competency. The average achievement of literacy competency in the content aspect is 61% for both informational texts and literary texts. The average competency achievements in the Cognitive Level aspect include 62% in the competency to access and find information (Level 1); competency to interpret and understand text content (Level 2) is 60%, and competency to evaluate and reflect on text content is 61%. The conclusion from the research results is that the literacy skills of high school students in Ogan Ilir Regency are still in the medium category. ABSTRAKTujuan penelitian adalah menganalisis capaian kemampuan literasi peserta didik hasil Asesmen Kompetensi Minimum (AKM) pada rapor pendidikan jenjang SMA. Metode penelitian yang digunakan adalah deskriptif kualitatif. Data yang dikumpulkan adalah capaian kemampuan literasi peserta didik hasil asesmen kompetensi minimum (AKM) pada rapor pendidikan jenjang SMA. Sampel penelitian diambil secara acak sebanyak 50% dari SMA di Kabupaten Ogan Ilir. Hasil penelitian menunjukkan bahwa rata-rata kemampuan literasi peserta didik SMA kabupaten Ogan Ilir mencapai kompetensi minimum sebanyak 54%, sisanya sebanyak 46% belum mencapai kompetensi minimum. Rata-rata capaian kompetensi literasi pada aspek konten, yaitu sebanyak 61 % baik pada teks informasi dan teks sastra. Rata-rata capaian kompetensi pada aspek Level Kognitif antara lain 62% pada kompetensi mengakses dan menemukan informasi (Level 1); kompetensi menginterpretasi dan memahami isi teks (Level 2) sebesar 60%, dan kompetensi mengevaluasi dan merefleksikan isi teks sebesar 61%. Kesimpulan dari hasil penelitian bahwa kemampuan literasi peserta didik SMA di Kabupaten Ogan Ilir masih tergolong dalam ketegori sedang.